Tourism itinerary recommendation using vehicle routing problem time windows and analytics hierarchy process - Nasution, Surya Michrandi; Septiawan, Reza Rendian; Azmi, Fairuz (Institute of Advanced Engineering and Science, 2024)
Bandung and Lembang are cities that are chosen by tourists as their destinations. Even though these cities are located side-by-side, each city has different characteristics. Bandung has many hotels and culinary spots, meanwhile, Lembang has many scenery spots. Tourists usually have limited time to visit all the destinations on holiday, which makes them choose several destinations. This paper proposes a tourism itinerary recommendation system based on the calculation of the most optimal route between destinations using the vehicle routing problem with time windows (VRPTW). Later, the optimal route is defined using the shortest path algorithm (Dijkstra). Data for the algorithm came from the collaboration between the several road information and criteria weights that are determined using the analytics hierarchy process (AHP). According to the simulation, the criteria weights are 6.9%, 62.7%, 18.6%, and 11.9% for route length, traffic condition, travel time, and weather condition, respectively. Moreover, the optimal number of tourism itinerary plans is 4 destinations. As the usage of computational resources, it takes 31.8% and 61.9% of CPU and memory usage. The time processing increases exponentially as the increment of the number of requested stops. The output of this research is expected to be a solution to the tourist itinerary plan.